Introduction to complex dynamics - Magreñán, Á. Alberto; Argyros, Ioannis K (Contemporary study of iterative methods: convergence, dynamics and applications, 2021)
In this chapter some dynamical concepts of complex dynamics that will be used in this book are presented. Moreover, some graphics illustrating the theoretical concepts are shown in order to let the reader understand them better.
Capítulo del libro "Contemporary study of iterative methods: convergence, dynamics and applications"
Keywords: complex dynamics; basins of attraction; parameter planes; WOS(2)